An analysis of haiku teaching discourse: From talking about to doing haiku - Hong-Nguyen (Gwen); Wolff- Michael Roth (Journal of Pedagogical Research, 2019)
Haiku have attracted interest among educators and teachers because of their aesthetic, intellectual, and therapeutic possibilities. Teachers whose interest is piqued might turn to online resources as haiku are not yet officially taught in teacher education programs. This paper is designed to investigate the discourses of resources concerning haiku that teachers might find online. Drawing on a discourse analysis, this study reveals two different discourses: (a) a talking about haiku discourse, which includes topics concerning theoretical aspects of haiku; and (b) a talking/doing haiku discourse, which concerns modelling haiku. The latter shows a movement toward an authentic practice in teaching haiku instead of using only a metalanguage approach. Based on the findings, an increased initial focus on the actual doing (talking) haiku is suggested preceding the elaboration of historical and other structural information to enhance its potential benefits.